PEMBERDAYAAN EKONOMI KERAKYATAAN MELALUI LEMBAGA KEUANGAN SYARÎ’AH - Wadhan - (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
UKM is the business maker of the lowest level marketing. The aim of the empowerment of UKM is that to grow and to accelerate a strong business ability, independent, and competition power against abroad products. It is a proper choice to use Syariah banking for UKM financing. Syariah banking has a great opportunity to develop macro banking in order to reform Indonesian economy.